One-pot synthesis of gold nanoparticle/molybdenum cluster/graphene oxide nanocomposite and its photocatalytic activity - Barras, Alexandre; Das, Manash R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Cordier, Stephane; Szunerits, Sabine; Boukherroub, Rabah (Applied Catalysis B-Environmental, 2013)
The paper reports on a facile one-pot synthesis of a tri-component gold nanoparticle/molybdenum cluster/graphene oxide (AuNPs@Mo-GO) nanohybrid composite. The synthetic methodology consists on direct UV irradiation of an aqueous solution containing graphene oxide (GO), Na-2[Mo6Br8(N-3)(6)], HAuCl4 center dot 3H(2)O and isopropanol at room temperature in air using a UV fiber lamp. The composite material exhibits very high photocatalytic activity for the degradation of rhodamine B under visible light irradation. The resulting nanohybrid material was characterized using Raman spectroscopy, UV-vis spectrometry, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). (c) 2012 Elsevier B.V. All rights reserved.
Keywords: gold nanoparticles; graphene oxide; Nanohybrid; Photodegradation; Rhodamine B; visible light; [Mo6Br8(N-3)(6)](2-)cluster

Nanodiamond particles/reduced graphene oxide composites as efficient supercapacitor electrodes - Wang, Qi; Plylahan, Nareerat; Shelke, Manjusha V.; Devarapalli, Rami Reddy; Li, Musen; Subramanian, Palaniappan; Djenizian, Thierry; Boukherroub, Rabah; Szunerits, Sabine (Carbon, 2014)
The paper reports on the preparation of reduced graphene oxide (rGO) modified with nanodiamond particles composites by a simple solution phase and their use as efficient electrode in electrochemical supercapacitors. The technique relies on heating aqueous solutions of graphene oxide (GO) and nanodiamond particles (NDs) at different ratios at 100 degrees C for 48 h. The morphological properties, chemical composition and electrochemical behavior of the resulting rGO/NDs nanocomposites were investigated using UV/vis spectrometry, Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, transmission electron microscopy (TEM) and electrochemical means. The electrochemical performance, including the capacitive behavior of the rGO/NDs composites were investigated by cyclic voltammetry and galvanostatic charge/discharge curves at 1 and 2 A g(-1) in 1 M H2SO4. The rGO/ND matrix with 10/1 ratio displayed the best performance with a specific capacitance of 186 +/- 10 F g (-1) and excellent cycling stability. (C) 2013 Elsevier Ltd. All rights reserved.

Glucose-derived porous carbon-coated silicon nanowires as efficient electrodes for aqueous micro-supercapacitors - Devarapalli, Rami Reddy; Szunerits, Sabine; Coffinier, Yannick; Shelke, Manjusha V.; Boukherroub, Rabah (ACS Applied Materials & Interfaces, 2016)
In this study, we report on carbon coating of vertically aligned silicon nanowire (SiNWs) arrays via a simple hydrothermal process using glucose as carbon precursor. Using this process, a thin carbon layer is uniformly deposited on the SiNWs. Under optimized conditions, the coated SiNWs electrode showed better electrochemical energy storage capacity as well as exceptional stability in aqueous system as compared to uncoated SiNWs. The as-measured capacitance reached 25.64 mF/cm(2) with a good stability up to 25000 charging/discharging cycles in 1 M Na2SO4 aqueous solution.
Keywords: carbon coating; glucose precursor; hydrothermal; microsupercapacitors; silicon nanowires

Reduced graphene oxide modified electrodes for sensitive sensing of gliadin in food samples - Chekin, Fereshteh; Singh, Santosh K.; Vasilescu, Alina; Dhavale, Vishal M.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (ACS Sensors, 2016)
Incidences of food allergies are on the rise, which can greatly affect the well-being of children as well as adults. Intolerance to gluten, a protein composite of gliadin and glutenin, present in wheat, barley, and rye and several cereals, can be the causative agent of celiac disease (CD) and other allergic reactions. A gluten-free diet has become essential for people affected by CD, and consequently, the amount of gluten in food products needs to be strictly controlled. In this paper, we report an electrochemical label-free immunosensor for ultrasensitive and specific detection of gliadin. The sensor takes advantage of the specific properties of porous reduced graphene oxide (prGO) covalently functionalized with anti-gliadin antibodies using 1-pyrenecarboxylic acid as linker molecule. Using differential pulse voltammetry (DPV) and [Fe(CN)6](3-/4-) as a redox probe, a decrease of current is linked to the presence of gliadin. The sensor achieved a detection limit of 1.2 ng mL(-1) over a 1.2-34 ng mL(-1) linear range with high selectivity. The advantages offered by this sensor are the possibility to regenerate the surface of the immunosensor, its rapid and ease of production, as well as applicability for the screening of gliadin concentrations in real food samples, as shown here.
Keywords: anti-gliadin antibody; food samples; gliadin; Immunosensor; Porous reduced graphene oxide

On demand electrochemical release of drugs from porous reduced graphene oxide modified flexible electrodes - Boulahneche, Samia; Jijie, Roxana; Barras, Alexandre; Chekin, Fereshteh; Singh, Santosh K.; Bouckaert, Julie; Medjram, Mohamed Salah; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
Despite the advantages of an electrochemical control for drug release, only a handful of electrochemical-based release systems have been developed so far. We report herein on the development of an electrochemically activatable platform for on-demand delivery of drugs. It is based on flexible gold thin film electrodes coated with porous reduced graphene oxide (prGO) nanosheets onto which the drug of interest has been integrated beforehand. Two different drugs are investigated here: ondansetron hydrochloride (ODS), a selective 5-HT3 receptor antagonist used for preventing nausea and vomiting caused by chemotherapy and radiotherapy, and ampicillin (AMP), an antibiotic to prevent and treat a number of bacterial infections such as respiratory tract infections, urinary tract infections, and meningitis. In the case of ODS, application of a negative potential bias of -0.8 V results in a sustained slow ODS release with an ODS flux of 47 mu g cm(-2) h(-1). In the case of AMP, we show that polyethyleneimine modified prGO (prGO/PEI) is an extremely efficient matrix. Upon the application of +0.8 V, 24% of AMP could be released from the electrical interface in a time span of 2 h. The released AMP kept its antibacterial activity as demonstrated by antimicrobial tests. These examples illustrate the major benefits of the developed approach for biomedical applications.

Efficient and durable oxygen reduction electrocatalyst based on CoMn alloy oxide nanoparticles supported over N-doped porous graphene - Singh, Santosh K.; Kashyap, Varchaswal; Manna, Narugopal; Bhange, Siddheshwar N.; Soni, Roby; Boukherroub, Rabah; Szunerits, Sabine; Kurungot, Sreekurnar (ACS Catalysis, 2017)
Transition metal oxide derived materials are very important for various applications, such as electronics, magnetism, catalysis, electrochemical energy conversion, and storage. Development of efficient and durable catalysts for the oxygen reduction reaction (ORR), an important reaction in fuel cells and metal air batteries, is highly desirable. Moreover, the futuristic catalysts for these applications need to be costeffective in order to ensure a competitive edge for these devices in the energy market. This article describes the synthesis of a cost-effective and efficient electrocatalyst for ORR It is based on supporting CoMn alloy oxide nano particles on N-doped porous graphene through a simple and scalable microwave irradiation method. Microwave irradiation was found to be very crucial for the fast creation of pores in the graphene framework with a concomitant formation of the CoMn alloy oxide nanoparticles. A series of catalysts have been synthesized by varying the Co:Mn ratio, among which, the one with the Co:Mn ratio of 2:1 [designated as CoMn/pNGr(2:1)] displayed remarkably higher ORR activity in 0.1 M KOH solution. It showed a similar to 60 mV potential shift with a low Tafel slope of 74 mV/decade, which is comparable to that derived from the commercial Pt/C catalyst. This high activity of CoMn/pNGr(2:1) has been credited to the cooperative effect arising from the metal entities and the defects present in the N-doped porous graphene. Finally, real system-level validations of the use of CoMn/pNGr(2:1) as cathode catalyst could be performed by fabricating and testing single-cells of an anion-exchange membrane fuel cell (AEMFC) and a primary Zn-air battery, which successfully demonstrated the efficiency of the catalyst to facilitate ORR in real integrated systems of the single-cell assemblies.
Keywords: anion-exchange membrane fuel cell; cooperativity effect; microwave synthesis; oxygen reduction reaction; porous N-doped graphene; Zn-air battery

Magnetic reduced graphene oxide loaded hydrogels: highly versatile and efficient adsorbents for dyes and selective Cr(VI) ions removal - Halouane, Fatima; Oz, Yavuz; Meziane, Dalila; Barras, Alexandre; Juraszek, Jean; Singh, Santosh K.; Kurungot, Sreekumar; Shaw, Pankaj K.; Sanyal, Rana; Boukherroub, Rabah; Sanyal, Amitav; Szunerits, Sabine (Journal of Colloid and Interface Science, 2017)
The formation of composites of reduced graphene oxide (rGO) and magnetic nanoparticles (MP) has flourished in recent years as they combine the advantages of both nanomaterials. Most of these composite materials are prepared by in situ formation of MP onto rGO or by the post-adsorption onto rGO. We report here on a simple and highly controlled method for the fabrication of different magnetic 3D rGO-loaded hydrogels. Cellulose bound magnetic nanoparticles (MP@cellulose) were synthesized by chemical co-precipitation and loaded together with rGO into poly(ethylene glycol) dimethacrylate based hydrogels during their fabrication using photo-polymerization. The magnetic rGO-loaded hydrogels proved to be highly adaptable to different applications. The as-formed composites allowed for efficient dye removal with an adsorption capacity of 111.9 +/- 4 mg g(-1) in the case of methylene blue (MB). Integration of poly(ethyleneimine) (PEI) allowed for the selective capturing of Cr6+ ions with an adsorption capacity of 313 12 mg g-1. Most importantly, independent of the application, the magnetic rGO-loaded hydrogel can be regenerated without loss of its adsorption capacity. (C) 2017 Elsevier Inc. All rights reserved.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. part 1: lysozyme aggregation at pH 2 and 7.4 - Vasilescu, Alina; Boulahneche, Samia; Chekin, Fereshteh; Gaspar, Szilveszter; Medjram, Mohamed Salah; Diagne, Abdou Aziz; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2017)
Protein instability due to misfolding and aggregation is of big concern for protein based therapeutics because it impacts the bioavailability and immunogenicity of such drugs. The development of simple and cost-effective methods for the analysis of pharmaceutical formulations, indicating the presence or absence of protein aggregates, is consequently of high importance. This work proposes a novel electrochemical interface based on porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) allowing for the early and sensitive identification of protein aggregation by following the change in the oxidative current of the proteins. The novelty of this work lies in the exploration of the ability of GC/prGO interfaces to capture different aggregation behaviors. Lysozyme is used as a model to follow by electrochemistry its aggregation at two pH values, pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Comparing the oxidation peak of lysozyme by differential pulse voltammetry (DPV) for different electrode architectures allowed validating the higher sensitivity of the GC/prGO interface versus bare glassy electrodes or electrodes coated with non-porous reduced graphene oxide. Parallel experiments were performed by fluorescence with thioflavin T, size exclusion chromatography and Atomic Force Microscopy (AFM) imaging. These tests further highlighted the usefulness of GC/prGO electrode to visualize in a fast and reliable manner the changes in the protein structure and the differences between the processes occurring at pH 2 and pH 7.4. In particular, the ability to emphasize changes related to the first steps in aggregation that could be indicative of the aggregation course, recommend the GC/prGO electrode in combination with DPV as a new analytical tool for aggregation studies of biopharmaceuticals. Part 2 of this work will demonstrate later the utility of this approach for the analysis of a fast acting injectable human insulin formulation, Humulin R, used for diabetes treatment as well as for calcitonin. (C) 2017 Elsevier Ltd. All rights reserved.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.

Nucleic aptamer modified porous reduced graphene oxide/MoS2 based electrodes for viral detection: application to human papillomavirus (HPV) - Chekin, Fereshteh; Bagga, Komal; Subramanian, Palaniappan; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Next to graphene nanomaterials, molybdenum disulfide (MoS2) offers large surface area that can enhance its biosensing performance. In this work, we investigate the performance of glassy carbon (GC) electrodes modified successively with porous reduced graphene oxide (prGO) and molybdenum sulfide (MoS2) for the sensitive and selective detection of the L1-major capsid protein of human papilloma virus (HPV). Owing to the difficulties to perform serological assays and HPV culture efficiently, tools based on molecular recognition are becoming of great importance. We developed here an electrochemical sensor for HPV upon covalent functionalization of the electrode with an aptamer Sc5-c3, a RNA aptamer targeted against the HPV-16 L1 protein. Using differential pulse voltammetry (DPV) and an optimized sensor interface, a linear relationship between the peak current density of a redox couple such as [Fe(CN)6]4- and the concentration of HPV-16 L1 proteins in the range of 0.2-2 ng mL(-1) (3.5 pM-35.3 pM) could be reached with a detection limit of 0.1 ng mL(-1) (1.75 pM). Cross-reactivity studies demonstrated high selectivity over potential interfering species such as HPV-16 E6, opening new opportunities of the developed concept for the development of point of care devices. (C) 2018 Elsevier B.V. All rights reserved.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 2: Application to the analysis of calcitonin containing pharmaceutical formulation - Vasilescu, Alina; Ye, Ran; Boulahneche, Samia; Lamraoui, Sabrina; Jijie, Roxana; Medjram, Mohamed Salah; Gaspar, Szilveszter; Singh, Santosh K.; Kurungot, Sreekumar; Melinte, Sorin; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2018)
In part 1 (A. Vasilescu et al., Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 1: Lysozyme aggregation at pH 2 and 7.4 Electrochem. Acta, 254 (2017) 375 -383) we proposed porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) in combination with differential pulse voltammetry as a new analytical tool for aggregation studies of proteins. Lysozyme was used as a model to follow its aggregation by electrochemical means at pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Part 2 of this work widens the scope of this approach by investigating a biopharmaceutical product, as the aggregation of peptide based drugs affects their therapeutic activity and can induce allergic reactions in patients. The salmon polypeptide calcitonin (sCT) was chosen as an example of a bioactive peptide with limited pharmaceutical potential due to a tendency to form cytotoxic aggregates and amyloid fibrils. For practical applications, screen printed electrodes (SPE) and flexible electrodes (FE) modified with polydiallyldimethylammonium (PDDA) and prGO by using the layer-by-layer deposition technique have been developed for the detection of sCT. The results indicate that these electrodes can differentiate between formation of amyloid aggregates of calcitonin (2 mg mL(-1)) in citrate buffer to no aggregation in acetate buffer. It was further demonstrated that these electrodes are able to analyze a pharmaceutical drug product of low potency, Miacalcic (8.3 mu g mL(-1)), where no aggregation was observed. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Calcitonin; Disposable electrodes; Electrochemistry; Porous reduced graphene oxide; Protein aggregation

Repeated photoporation with graphene quantum dots enables homogeneous labeling of live cells with extrinsic markers for fluorescence microscopy - Liu, Jing; Xiong, Ranhua; Brans, Toon; Lippens, Saskia; Parthoens, Eef; Zanacchi, Francesca Cella; Magrassi, Raffaella; Singh, Santosh K.; Kurungot, Sreekumar; Szunerits, Sabine; Bove, Hannelore; Ameloot, Marcel; et al. (Light-Science & Applications, 2018)
In the replacement of genetic probes, there is increasing interest in labeling living cells with high-quality extrinsic labels, which avoid over-expression artifacts and are available in a wide spectral range. This calls for a broadly applicable technology that can deliver such labels unambiguously to the cytosol of living cells. Here, we demonstrate that nanoparticle-sensitized photoporation can be used to this end as an emerging intracellular delivery technique. We replace the traditionally used gold nanoparticles with graphene nanoparticles as photothermal sensitizers to permeabilize the cell membrane upon laser irradiation. We demonstrate that the enhanced thermal stability of graphene quantum dots allows the formation of multiple vapor nanobubbles upon irradiation with short laser pulses, allowing the delivery of a variety of extrinsic cell labels efficiently and homogeneously into live cells. We demonstrate high-quality time-lapse imaging with confocal, total internal reflection fluorescence (TIRF), and Airyscan super-resolution microscopy. As the entire procedure is readily compatible with fluorescence (super resolution) microscopy, photoporation with graphene quantum dots has the potential to become the long-awaited generic platform for controlled intracellular delivery of fluorescent labels for live-cell imaging.

Sensitive electrochemical detection of cardiac troponin I in serum and saliva by nitrogen-doped porous reduced graphene oxide electrode - Chekin, Fereshteh; Vasilescu, Alina; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Iancu, Madalina; Badea, Gabriela; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Cardiovascular diseases pose one of the highest mortality risks among all diseases in developed countries, steadily increasing the burden on the health systems. Early diagnosis of cardiovascular diseases has consequently become highly important to decrease mortality and to use more adapted therapeutic decisions. We demonstrate here the utility of nitrogen-doped reduced graphene oxide (N-prGO) for detecting and quantifying of cardiac troponin I (cTnI), a key human cardiac protein biomarker, under physiologically relevant conditions. Non-covalent modification of N-prGO by 1-pyrenecarboxylic acid (py-COOH) and poly(ethylene glycol) modified pyrene (py-PEG) ligands allowed the covalent integration of Tro4 aptamer, known for its high selectivity towards cTnI. Using differential pulse voltammetry (DPV), a label-free electrochemical sensor for cTnI for concentrations down to 1 pgmL(-1) in human serum could be obtained. This sensitive detection arises from the integration of a porous nanomaterial with excellent electrochemical properties being easily amendable to site-specific surface modification. (C) 2018 Elsevier B.V. All rights reserved.

Graphene-modified electrodes for sensing doxorubicin hydrochloride in human plasma - Chekin, Fereshteh; Myshin, Vladyslav; Ye, Ran; Melinte, Sorin; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Analytical and Bioanalytical Chemistry, 2019)
Doxorubicin (DOX), an anthracycline molecule, is currently one of the most widely used anticancer drugs in clinics. Systematic treatment of patients with DOX is known to be accompanied by several unpleasant side effects due to the toxicity of the drug. Thus, monitoring of DOX concentration in serum samples has become increasingly important to avoid side effects and ensure therapeutic efficiency. In this study, we discuss the construction of a disposable electrochemical sensor for the direct monitoring of DOX in clinical blood samples. The sensor is based on coating a gold electrode in a flexible integrated electrode construct formed on polyimide sheets using photolithography, with nitrogen-doped reduced graphene oxide (N-rGO) suspended in chitosan. Under optimized conditions, a linear relationship between the oxidative peak current and the concentration of DOX in the range of 0.010-15M with a detection limit of 10nM could be achieved. The sensor was adapted to monitor DOX in serum samples of patients under anticancer treatment.
Keywords: Disposable electrodes; doxorubicin; Nitrogen-doped reduced graphene oxide; Serum

High-energy flexible supercapacitor-synergistic effects of polyhydroquinone and RuO2 center dot xH(2)O with microsized, few-layered, self-supportive exfoliated-graphite sheets - Muniraj, Vedi Kuyil Azhagan; Dwivedi, Pravin Kumari; Tamhane, Parikshit Shivaji; Szunerits, Sabine; Boukherroub, Rabah; Shelke, Manjusha Vilas (ACS Applied Materials & Interfaces, 2019)
An effective and straightforward route for tailoring the self-supporting, exfoliated flexible graphite substrate (E-FGS) using electrochemical anodization is proposed. E-FGS has essential features of highly exfoliated, few-layered, two-dimensional graphite sheets with the size of several tens of micrometers, interconnected along the axis of the substrate surface. The novel hierarchical porous structural morphology of E-FGS enables large active sites for efficient electrolyte ion and charge transport when used as electrode material for a supercapacitor. In order to effectively utilize this promising E-FGS electrode for energy storage purpose, a ternary composite is further synthesized with pseudocapacitive polyhydroquinone (PHQ) and hydrous RuO2 (hRO). hRO is synthesized via a sol-gel route, while electropolymerization is utilized for the electrodeposition of PHQ over E-FGS. Ultimately, the fabricated self-supporting E-FGS-based flexible supercapacitor is capable of delivering areal specific capacitance values as high as 378 mF cm(-2) at a current density of 1 mA cm(-2). Addition of the pseudocapacitive component to the E-FGS texture leads to similar to 10 times increase of the electrochemical charge storage capability. The imposition of mechanical forces to this flexible supercapacitor device results in trivial changes in electrochemical properties and is still capable of retaining 91% of the initial specific capacitance after 10 000 cycles. Alongside, the fabricated symmetrical solid-state flexible device exhibited a high energy density of 8.4 mu Wh cm(-2). The excellent performance along with the ease of synthesis and fabrication process of the flexible solid-state supercapacitor device using PHQ/hRO/E-FGS holds promise for large-scale production.
Keywords: graphite exfoliation; polyhydroquinone; ruthenium oxide; solid-state flexible supercapacitor; Ternary Composite

Enhanced electrocatalytic activity of PtRu/nitrogen and sulphur co-doped crumbled graphene in acid and alkaline media - Pang, Liuqing; Miao, Yuanyuan; Bhange, Siddheshwar N.; Barras, Alexandre; Addad, Ahmed; Roussel, Pascal; Amin, Mohammed A.; Kurungot, Sreekumar; Szunerits, Sabine; Boukherroub, Rabah (Journal of Colloid and Interface Science, 2021)
The low mass activity and high price of pure platinum (Pt)-based catalysts predominantly limit their large-scale utilization in electrocatalysis. Therefore, the reduction of Pt amount while preserving the electrocatalytic efficiency represents a viable alternative. In this work, we prepared new PtRu2 nanoparticles supported on sulphur and nitrogen co-doped crumbled graphene with trace amounts of iron (PtRu2/PF) electrocatalysts. The PtRu2/PF catalysts exhibited enhanced electrocatalytic performance and stability for the hydrogen evolution reaction (HER) at pH = 0. Moreover, the prepared PtRu2/PF electrocatalyst displayed higher HER activity than commercial 20% Pt/C. The PtRu2/PF catalyst achieved a current density of 10 mA cm(-2) at an overpotential value of only 22 mV for HER, performing better activity than many other Pt-based electrocatalysts. Besides, the PtRu2/PF revealed a good performance for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. The PtRu2/PF catalyst recorded a current density of 10 mA cm(-2) at an overpotential of only 270 mV for OER in KOH (1.0 M) solution and an onset potential of 0.96 V vs. RHE (at 1 mA cm(-2)) for ORR in KOH (0.1 M) solution. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: HER; OER; ORR; PtRu2; Sulphur and nitrogen co-doped crumbled graphene

Single-step synthesis of exfoliated Ti3C2Tx MXene through NaBF4/HCl etching as electrode material for asymmetric supercapacitor - Ghosh, Meena; Szunerits, Sabine; Cao, Ning; Kurungot, Sreekumar; Boukherroub, Rabah (ChemistrySelect, 2022)
Two-dimensional Ti3C2Tx MXene, derived from the parent Ti3AlC2 phase, is considered a promising electrode material for electrochemical energy storage applications. Ti3C2Tx MXene synthesis methods often employ concentrated hydrofluoric acid (HF), which is harsh, corrosive, and hazardous to the environment. Herein, we report the preparation of Ti3C2Tx MXene following a new synthetic route under a mild reaction condition comprising an aqueous solution of NaBF4 and HCl. This etching environment at a moderate temperature of 130 degrees C effectively removes the Al layer of the Ti3AlC2 precursor, assisted by the in situ formed HF in the reaction medium. Electron microscopy images of the as-prepared Ti3C2Tx (MX-130) reveal a partially exfoliated nanosheet-like morphology. The material displays a specific capacitance of 262 F g(-1) (three-electrode assembly, 1 A g(-1), -0.85 to -0.25 V vs. Hg/Hg2SO4) in 1 M H2SO4 electrolyte. The achieved specific capacitance is superior to that of Ti3C2Tx prepared via the common HF-treatment (25 F g(-1)). Additionally, the potential application of the optimized MXene as a negative electrode material is demonstrated in a quasi-solid-state RuO2|MX-130 asymmetric supercapacitor device.
Keywords: asymmetric supercapacitor; Electrochemistry; Fluoride salt etchant; Layered electrode materials; Transition metal carbides